Comparison of Alternatif Planning Framework and Demand Modelling Methodologies of Mass Transit System Proposal For Jakarta - Karsaman, Rudy Hermawan (Journal of Regional and City Planning, 1999)
Using three different proposals made for Jakarta during 1988-1992 as a ase study, this work investigates the formulation of mass transit system proposals in Jakarta with the objectives of comparing alternative transportation demand modelling methods, assessing their strengths and weaknessess and recommending the most suitable ones to be adapted. The results indicate that, in the general context of developing countries and for pre-feasibility level, simple methods and models still seem more appropriate due to the lack of reliable data and expertise, fast changing developments and high uncertainties. Despite the development of new models and methods in developed countries, their application in developung countries might need to be adjusted and simplified due to the different environment. More specifically, each study has its own strengths and weaknesses, therefore their combination might results in better outcome.